PELESTARIAN TARI GALOMBANG DUO BALEH MELALUI PENCIPTAAN TARI TATAGOK - Pamela Mikaresti; Herlinda Mansyur; Elizar Elizar (Gorga : Jurnal Seni Rupa, 2023)
The existence of the "Galombang Duo Baleh" Dance among the young generation of cultural heirs in Nagari Pitalah is in an alarming condition. It is clear that the lack of interest of the younger generation in learning and preserving the "Galombang Duo Baleh" Dance is because many other interesting things can be played from home without having to gather at the Sasaran. It is evident that Sasaran has begun to be abandoned as a forum for learning various things including silat and the "Galombang Duo Baleh" Dance as games and entertainment for village children in the past. The reasons mentioned above are inseparable from developments in science, technology and art. It is evident that the younger generation prefers online games which are accessed from their respective devices, watching entertainment from YouTube, to being busy in establishing social relations through social media such as TikTok, Instagram, Twitter, Facebook and other social media because they are more interesting. To overcome this, it is necessary to have a new innovationÂ that can attract the interest of the younger generation in learning traditional dance so that it continues to live and develop in the life of the people who inherit it. The dance creation method uses the theory of the stages of creating dance works referring to Alma M Hawkins' theory of motion exploration, motion improvisation, motion composition and motion evaluation. The result of the creation of the development of the "Galombang Duo Baleh" Dance is the "Tatagok" Dance. "Tatagok" dance is a newly created dance that develops the basic movements of the "Galombang Duo Baleh" dance. Learning the "Tatagok" Dance means participating in learning the basics of the "Galombang Duo Baleh" Dance, because the movements of the "Tatagok" Dance come from the basic movements of the "Galombang Duo Baleh" Dance which are packaged in a new form by considering the knowledge of dance composition to make it look more attractive.Kata Kunci: preservation, traditional dance, creation dance.Â AbstrakEksistensi Tari Galombang Duo Baleh diantara generasi muda pewaris budaya di Nagari Pitalah berada dalam kondisi mengkhawatirkan. Terlihat jelas bahwa kurangnya minat generasi muda untuk mempelajari dan melestarikan Tari Galombang Duo Baleh karena banyak hal menarik lainnya bisa dimainkan dari rumah tanpa harus berkumpul di Sasaran. Terbukti bahwa Sasaran sudah mulai ditinggalkan sebagai wadah mempelajari berbagai hal termasuk silat danÂ  gerak Tari Galombang Duo Baleh sebagai permainan dan hiburan anak nagari dahulunya. Penyebab hal yang disebutkan di atas tidak terlepas dari perkembangan ilmu pengetahuan, teknologi dan seni, terbukti bahwa generasi muda lebih menyukai permainan online yang diakses dari gawai masing-masing, menonton hiburan dari Youtube, hingga sibuk dalam menjalin hubungan sosial melalui media sosial seperti TikTok, Instagram, Twitter, Facebook dan media sosial lainnya karena lebih menarik. Untuk mengatasi hal demikian, maka perlu adanya sebuah inovasi baru yang bisa menarik minat generasi muda dalam mempelajari tari tradisional agar tetap hidup dan berkembang dalam kehidupan masyarakat pewarisnya. Metode penciptaan tari menggunakan teori Tahapan penciptaan karya tari merujuk teori Alma M Hawkins adalah eksplorasi gerak, improvisasi gerak, komposisi gerak dan evaluasi gerak, Hasil penciptaan pengembangan Tari Galombang Duo Baleh adalah Tari Tatagok. Tari Tatagok adalah tari kreasi baru pengembangan gerak dasar Tari Galombang Duo Baleh. Mempelajari Tari Tatagok, berarti ikut mempelajari pakem-pakem Tari Galombang Duo Baleh, sebab gerakan Tari Tatagok berasal dari gerak dasar Galombang Duo Baleh yang dikemas dalam bentuk baru dengan mempertimbangkan ilmu komposisi tari agar terlihat lebih menarik.Â Authors:Pamela Mikaresti : Universitas TerbukaHerlinda Mansyur : Universitas Negeri PadangElizar : Institut Seni Indonesia PadangpanjangÂ References:Dewi, F. S. P. (2022). Konsep Perkembangan KognitifÂ Anak Usia Sekolah Dasar dalam Implementasi Pembelajaran Menurut Teori Jeas Piaget (Telaah Buku Teori Perkembangan Kognitif Jean Peaget). Lampung: UIN Raden Intan Lampung.Hajizar, H. (2022). â€œPewarisan Tariâ€. HasilÂ Wawancara Pribadi: 23 April 2022, Padangpanjang.Hidayat, R. (2022). â€œPewarisan Tariâ€. HasilÂ Wawancara Pribadi: 24 April 2022, Padangpanjang.Mikaresti, P., Mikaris, Y., & Tamara, C. (2020). Symbolic Meaning of Dance with Masks Peopleâ€™s Life from Muaro/Jambi District. InÂ Proceeding International Conference on Malay IdentityÂ (Vol. 1, pp. 162-174).Mikaresti, P., & Mansyur, H. (2022, April). Creating an Indonesian Archipelago Creation Dance for Elementary School-Aged Children. InÂ International Conference on Elementary EducationÂ (Vol. 4, No. 1, pp. 542-552).Przybylski, A. K., & Weinstein, N. (2017). A Large-Scale Test of the Goldilocks Hypothesis: Quantifying the Relations Between Digital-Screen Use and the Mental Well-Being of Adolescents.Â Psychological Science,Â 28(2), 204-215.Ramlan, P. M., Bahar, M., & Gunawan, I. (2018). Tari Skin Sebagai Identitas Kehidupan Masyarakat Kabupaten Merangin.Â Titian: Jurnal Ilmu Humaniora,Â 2(02), 253-268.Suharto, B. (1985). Komposisi Tari Sebuah PetunjukÂ Praktis. Yogyakarya: Ikalasti.Susanti, M., Erlinda, E., & Sastra, A. I. (2016). Estetika Main Bungo dalam Penyajian Galombang Duobaleh di Nagari Pitalah Kabupaten Tanah Datar.Â Bercadik: Jurnal Pengkajian dan Penciptaan Seni,Â 4(1), 13-28.Hadi, Y. S. (2014). Koreografi: Bentuk, Teknik, Isi. Yogyakarta: Cipta Media.Â Â